The antiplaque/anticariogenic efficacy of Salvadora persica (Miswak) mouthrinse in comparison to that of chlorhexidine: a systematic review and meta-analysis - Elaf Jassoma; Lina Baeesa; Heba Sabbagh (BMC, 2019)
Abstract Background The plant Salvadora persica (miswak) has a long history of use in oral hygiene. Associations between the use of Salvadora persica and decreased oral bacteria numbers and plaque scores have been reported. This systematic review and meta-analysis assessed the ability of Salvadora persica mouthrinses to reduce plaque/cariogenic bacteria, in comparison to that of chlorhexidine and/or placebo rinses. Methods A comprehensive literature search for clinical trials reporting the use of Salvadora persica rinses as an antibacterial and/or antiplaque agent in comparison with chlorhexidine and/or placebo rinses was conducted, with no restriction to language. MEDLINE-PubMed, Cochrane Central Register of Controlled Trials, Wiley Online Library, ScienceDirect, and Google Scholar databases were searched to include all articles published up to December 2018. Based on inclusion/exclusion criteria, data were extracted from the identified reports by two independent reviewers. The primary and secondary outcomes measured from the eligible studies were mean plaque scores and mean cariogenic bacterial counts, respectively. Risk of bias of these studies was assessed. A statistical test of homogeneity was used to determine if the results of the separate studies could be combined. Based on the chi-square test, an inconsistency coefficient was computed (I2 statistic). Sensitivity analyses using subgroups and homogeneity evaluation were conducted. Results A total of 1135 potentially eligible articles were identified, of which 19 were eventually included in the qualitative analysis whereas 18 were included in the quantitative meta-analysis. The meta-analysis showed that Salvadora persica rinses exhibited strong antiplaque effects (P < 0.00001, MD: 0.46, and 95% CI: 0.29 to 0.63). In addition, it had statistically significant anti-streptococcal (P < 0.0001, MD: -1.42, and 95% CI: -2.08 to − 0.76) and anti-lactobacilli effects (P < 0.00001, MD: -1.12, and 95% CI: -1.45 to − 0.79) when compared to placebo. However, its effects were inferior compared to those by chlorhexidine rinse (P = 0.04, MD: 0.19, and 95% CI: 0.01 to 0.37). Subgroup analyses yielded results similar to those prior to subgrouping. Conclusion The use of Salvadora persica extract was associated with a significant reduction in the plaque score and cariogenic bacterial count. Although, this reduction was lower than that achieved with the gold standard chlorhexidine mouthwash, Salvadora persica-containing rinse could be considered as a suitable oral hygiene alternative for use in individuals of all ages, socioeconomic backgrounds, and health conditions especially as a long-term measure due to its efficacy, safety, availability, cost-effectiveness, and ease of use.